EP294 Comparison of triage management between p16INK4a/Ki67 dual staining and HR-HP test in patients with cervical cytology ASC-US and LSIL. (1st November 2019) - Geng, L; Li, Y; Ge, X; You, K; Guo, Y
Abstract : Introduction/Background: To compare the triage management between p16 INK4a /Ki67 dual staining and HR-HPV test detection in patients with cervical cytology ASC-US and LSIL. Methodology: 143 patients with cervical cytology results as ASC-US and LSIL were enrolled in the gynecological clinic of the Third Hospital of Peking University from June 2016 to July 2018. The average age was 38.83 years. All the participants underwent dual staining test of p16 INK4a /Ki67, HR-HPV test, colposcopy and biopsy. CINtec PLUS kit (Roche, USA) was used for p16 INK4a /Ki67 dual staining and Cobas 4800 detection system (Roche, USA) was used for HR-HPV test. Results: A total of 143 participants were enrolled with 86 ASC-US cases (86/143, 60.1%)and 57 LSIL cases (57/143, 39.9%). Cervical biopsy results showed that 35 cases (35/143, 24.5%)were ≤CIN1, 72 cases (72/143, 50.3%) were CIN2, 29 cases (29/143, 20.3%) were CIN3 and 7 cases (7/143, 4.9%) were cervical cancer. In patients with cervical cytology results as ASC-US and LSIL, the sensitivity of p16 INK4a /Ki67 dual staining and HR-HPV test for detection CIN 2 or above were 85.2% and 75.4% (p=0.078), with the specificity of 54.3% and 22.2% (p<0.001), and the AUC of ROC curve was 0.697 (95% CI 0.615–0.771), 0.504 (95% CI 0.419–0.588) (P<0.001), and referral rate of colposcopy was 75.5% and 93.7% (p=0.001). Conclusion: In patients with cervical cytology ASC-US and LSIL, p16 INK4a /Ki67 dual staining shows a higher specificity in detecting lesions of CIN2 or above and lower referral rate of colposcopy than that of HR-HPV test, and the sensitivity was also higher in p16 INK4a /Ki67 dual staining. In patients with cytological ASC-US and LSIL, p16 INK4a /Ki67 dual staining triage was more effective than HR-HPV test in detecting CIN2 or above lesions. Disclosure: Nothing to disclose.